IMPLIKASI PEMBERLAKUAN UNDANG-UNDANG CIPTA KERJA TERHADAP PERLINDUNGAN HUKUM PEKERJA HARIAN LEPAS - Kurniasih, Esy; Milandry, Anggraini Dwi (Yayasan Pendidikan Islam Almatani, 2022)
The relationship between employers and workers is ideally a win-win relationship, but in reality the position of workers often has a more vulnerable (low) position than the employer. Therefore, to form a fair employment relationship, an employment agreement is needed. Freelance Daily Workers (PHL) Agreement is one type of work agreement regulated in Law No. 13 of 2003 concerning Manpower. However, in October 2020 the Indonesian government has enacted Law No. 11 of 2020 concerning Job Creation which is carried out with the concept of Omnibus LawThe enactment of the Job Creation Law makes regulations derived from Law No. 13 of 2003, namely Ministerial Decree Number: KEP.100 / MEN / VI / 2004 concerning Provisions for the Implementation of Specific Time Work Agreements, become does not apply. This research aimed to describe the issues Implications of The Job Creation Law Enactment On The Legal Protection Of Freelance Daily Work. This research used the normative juridical method with a statutory. The result of this research is, in theory, the Omnibus Law’s Enactment in the realm of employment has several positive implications for rules related to the legal protection of Freelance Daily Workers (PHL). This is related to legal protection of the status of freelance daily workers, legal protection of wage certainty for freelance daily workers, and legal protection of social security for freelance daily workers.